PROSES POLITISASI DANA PUNIA PADA PEMILIHAN UMUM KEPALA DAERAH KABUPATEN BADUNG TAHUN 2015 DI DESA PECATU - Bhaskara Wardana, I Putu Panji; Putra Erawan, I Ketut; Andreas Noak, Piers (Jurnal Nawala Politika, 2016)
ABSTRACT Dana punia activities that are not classified into the money politic activities, became the basis of the highlights of this study to show how the dana punia have been politicized to hide money politics. As a step theoretical, this study uses the theory of democracy collusive Dan Slater, who raises collusion and twilight institution theory in doing analysis of the research results. The method used in this research is descriptive qualitative method, while data collecting technique through interview (interview), chat with many people (discorse) and document analysis. Field findings indicate dana punia as a means of communication instruments candidates to obtain the support and voice of the community. Furthermore, there are no rules that prohibit their dana punia activities at the election moments. In addition to the initiative of candidates, dana punia was needed by the people for ceremonial purposes, repair temples facilities. The theoretical implications to shows that the theory of collusive democratic and twilight institution affect the voters and community support for election candidates who give dana punia in head district of Badung Regency General Election in 2016 in Pecatu village. Keywords: Dana Punia, Politicization, Election